Interaction of the N- and C-terminal Autoregulatory Domains of FRL2 Does Not Inhibit FRL2 Activity - Vaillant, Dominique C.; Copeland, Sarah J.; Davis, Chris; Thurston, Susan F.; Abdennur, Nezar; Copeland, John W. (The Journal of biological chemistry, 2008)
Formin homology proteins are a highly conserved family of cytoskeletal remodeling proteins best known for their ability to induce the formation of long unbranched actin filaments. They accomplish this by nucleating the de novo polymerization of F-actin and also by acting as F-actin barbed end “leaky cappers” that allow filament elongation while antagonizing the function of capping proteins. More recently, it has been reported that the FH2 domains of FRL1 and mDia2 and the plant formin AFH1 are able to bind and bundle actin filaments via distinct mechanisms. We find that like FRL1, FRL2 and FRL3 are also able to bind and bundle actin filaments. In the case of FRL3, this activity is dependent upon a proximal DAD/WH2-like domain that is found C-terminal to the FH2 domain. In addition, we show that, like other Diaphanous-related formins, FRL3 activity is subject to autoregulation mediated by the interaction between its N-terminal DID and C-terminal DAD. In contrast, the DID and DAD of FRL2 also interact in vivo and in vitro but without inhibiting FRL2 activity. These data suggest that current models describing DID/DAD autoregulation via steric hindrance of FH2 activity must be revised. Finally, unlike other formins, we find that the FH2 and N-terminal dimerization domains of FRL2 and FRL3 are able to form hetero-oligomers.